Indirect search of heavy neutral leptons using the DUNE near detector - Carbajal, S.; Gago, A. M. (Frontiers in Physics, 2024)
We evaluate the potential of the DUNE Near Detector (DUNEND) for establishing bounds for heavy neutral leptons (HNL). This is achieved by studying how the presence of HNLs affects the production rates of active neutrinos, therefore, creating a deficit in the neutrino charged current (CC) events at the LArTPC of the DUNEND. The estimated bounds on HNLs are calculated for masses between 1 eV and 500 MeV. We consider 10 years of operation (5 in neutrino and antineutrino mode) and obtain limits offor masses below 10 MeV and a 5%(20%) overall normalization uncertainty in the neutrino charged current event rates prediction. These limits, within the region of masses below 2(10) MeV, are better than those that can be achieved by DUNE direct searches for the case of a 5%(20%) uncertainty. When a conservative 20% uncertainty is present, our limits can only improve current constraints on |Ue4|^2 by up to a factor of 3 in a small region around 5 eV and set limits on |Uµ4|^2 in a mass region free of constraints (40 eV -1 MeV).